2010
DOI: 10.1007/s11224-010-9665-z
|View full text |Cite
|
Sign up to set email alerts
|

From Democritus to Schrödinger: a reflection on quantum molecular modeling

Abstract: This review describes the saga of the atom and molecules, from the atomic concept as it was introduced 25 centuries ago by Leucippus and Democritus, to the modern Quantum Molecular Modeling. Quantum methods that have given rise to the contemporary Molecular Modeling are briefly presented. Chosen examples illustrate the performance and the predictions of Quantum Modeling in the following topics: conformational analysis, electrostatics, molecular spins and radicals, infrared and Raman spectra, thermochemistry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Experimentally, it has been shown that gaseous HCN is partially polymerized at pressures beyond 1.3 GPa [24,25]. While there are many static calculations on the stability of HCN clusters [23,[26][27][28][29], only a few theoretical studies are available on the dynamic formation of HCN polymers [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it has been shown that gaseous HCN is partially polymerized at pressures beyond 1.3 GPa [24,25]. While there are many static calculations on the stability of HCN clusters [23,[26][27][28][29], only a few theoretical studies are available on the dynamic formation of HCN polymers [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…HOMO represents the ability to donate an electron, and LUMO acts as an electron acceptor. Therefore, the molecular properties describing the global reactivity and local selectivity of the molecule under study, such as electron affinity A = -E LUMO , ionization potential I = -E HOMO , electronegativity χ = (I + A)/2, and hardness η = (I -A)/2, may be assessed from the HOMO and LUMO energy values [27][28][29][30]. For thymogen, these calculated parameters are as follows: A = 1.710 eV, I = 6.278 eV, χ = 3.994 eV, η = 2.284 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Vasilescu and Adrian-Scotto [309] in their paper review the development of quantum molecular modeling from historical approach and atom concept to two essential ways used today, the ab initio and DFT methods with which, among others, conformational analysis, electrostatics, molecular spins and radicals, infrared and Raman spectra, thermochemistry, and electrophilicity properties can be derived.…”
Section: Issuementioning
confidence: 99%